Chemoradiation for invasive cervical cancer in elderly patients: outcomes and morbidity. Issue 1 (1st January 2008) - Goodheart, M.; Jacobson, G.; Smith, B. J.; Zhou, L.
Abstract : Age may impact survival and treatment in cervical cancer patients. We sought to determine if treatment and survival were different in elderly patients and whether chemoradiation increased morbidity. We performed a retrospective chart review to identify patients treated with definitive radiation therapy at the University of Iowa Hospitals and Clinics between 1997 and 2001. Three hundred sixty-four patients had a new diagnosis of invasive cervical cancer, of which 150 patients were treated with radiation. We excluded patients treated postoperatively or with palliative intent, leaving 96 patients treated with definitive radiation therapy. Patients were divided into two age categories: elderly (≥65) and nonelderly (<65). We compared these groups with respect to treatment received, morbidity, and survival. Sixty-nine (72%) women were less than 65 years old, and 27 (28%) women were greater than or equal to 65 years old. Chemoradiation was associated with decreased mortality ( P < 0.01). The decrease in mortality did not differ between the two age cohorts (all causes: P = 0.66; cancer specific: P = 0.65), nor was there a difference in the complication rate due to chemoradiation ( P = 0.70). Although elderly patients were more likely to be diagnosed with nonsquamous histologies ( P < 0.01), their odds of receiving chemoradiation were 0.35 (95% CI: 0.13–0.90) times the odds for nonelderly. Elderly cervical cancer patients more often have nonsquamous histology and are likely to receive only radiation therapy compared to younger patients. Treatment with chemoradiation was associated with similar survival increases in both age cohorts. Complication rates between the two were similar. Chemoradiation should be considered in elderly patients with invasive cervical cancer.